Profiling of Oral Squamous Cell Carcinoma of Lower Assam Region – A Hospital-Based Retrospective Study - Debojyoti Roy; Thamizholi Selvaraju; Bharadwaj Bordoloi; BahniSikha Pathak; Divjot Ahluwalia (Contemporary Clinical Dentistry)
Background: Oral cancer is one of the ten most common cancers worldwide and the sixth most common type of all cancer in India. Among the oral malignancies, oral squamous cell carcinoma (OSCC) is the most common, accounting for more than 90% of oral cancer and hence a significant public health concern. Aim: The aim of this study was to evaluate clinicopathological and demographic profiling of OSCC in a district and adjacent area of lower Assam. Settings and Design: This was a retrospective observational study. Materials and Methods: A total of 140 histologically confirmed OSCC patients diagnosed at the Regional Cancer Centre in the district between the period 2022 April and 2023 October constitute our study sample size in this study. The duration of the study was 1½ years. Statistical Analysis: The clinical and histopathological features were analyzed using descriptive statistics. Statistical Package for the Social Science (SPSS) version 23.0 was used. Results: OSCC constitutes 23.97% of head-and-neck cancer. The incidence of OSCC was higher in males. The highest number of patients was in the age group of 50–59. The most common site of OSCC was the buccal mucosa followed by the tongue. Most of the cases were well differentiated, the number being 82 (58.57%). Most of the patients were in Stage III and Stage IV. Conclusions: The present study highlights that in the lower Assam region, the majority of the OSCC patients are middle-aged male patients with advanced stages of OSCC. The findings from the present study can be used to compare the scenario of OSCC in other parts of Assam and North East India and also can be used for a follow-up study.